Electrical study of ZrO2/Si system formed at different oxidation/nitridation temperatures for extended duration in N2O ambient - Wong, Y.H.; Cheong, K.Y. (Materials Research Society, 2013)
Electrical properties of ZrO2 formed by simultaneous oxidation and nitridation of sputtered Zr thin films on Si have been systematically investigated. Various oxidation/nitridation temperatures (500, 700, 900, and 1100 °C) have been carried out in N2O ambient for an extended time of 20 min. Results indicated that the sample oxidized and nitrided at 700 °C possessed the highest effective dielectric constant of 18.22 and electrical breakdown field of 10.7 MV/cm at a current density of 10−6 A/cm2. This is attributed to the lowest effective oxide charge, interface-trap density, and total interface-trap density. The Fowler–Nordheim tunneling mechanism has been investigated for all samples and the highest value of barrier height extracted between the conduction band edges of oxide and semiconductor was 1.22 eV.